Nuevas tecnologías de información y comunicación para la enseñanza de la Odontología: Algunas consideraciones para los docentes - Maroto M., Orlando (2011)
The introduction of new information and communication technologies (ICT) within the educational process seems to represent a high point of educational innovations and thus attract the attention of many as an answer to educational problems facing the society of knowledge. Sometimes solutions are seem to be “fashionable”, as far as education is concerned, but leave out many aspects that can then became a cause failure of well-intentioned educational strategies. For topics in dentistry, there are websites with structures designed to attract the professional to a continuing education through online courses that do not require them to travel to other locations for training or to obtain information without having to change their professional schedules. The use of other tools such as multimedia undergraduate and graduate education and use of forums and blogs for learning through interaction with other peers or the teacher is discussed. This article is an analysis of the role of ICT’s as educational innovations in the field of dentistry, with suggestions to the reader of some strategies to use in a consensual manner and to try to find the best results in the teaching and learning process.